2019
DOI: 10.23923/pap.psicol2019.2893
|View full text |Cite
|
Sign up to set email alerts
|

¿Cómo funciona el autocontrol? Un análisis de la compra por impulso

Abstract: tudies in everyday life show that people resist against impulses that tempt them to go back to sleep, eat delicious snack foods, engage in inappropriate sexual behavior and impulse buying (Baumeister, Vohs, & Tice, 2007; Hagger, Wood, Stiff, & Chatzisarantis, 2010; Vohs & Faber, 2007). "From a self-control researcher's perspective, one challenge is to make sure that the research does indeed address how people deal with temptation, successfully or unsuccessfully" (Hofmann & Kotabe, 2012, p. 711). Much progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
(149 reference statements)
1
7
0
1
Order By: Relevance
“…This means that an individual who has a tendency to buy impulsively will create an impulsive buying behavior in another individual. This study is in accordance with the previous research by Moayery, Narvaiza Cantín, and Gibaja Martíns (2019) where the tendency to buy impulsively is the most influential factor in determining an individual's impulsive buying behavior. Atulkar & Kesari (2018) also revealed that impulse buying tendencies are closely related to consumer impulse buying behavior, where high impulse buying tendencies can make consumers decide to make purchases spontaneously, without any hesitation, and unexpectedly.…”
Section: Influence Of Impulse Buying Tendency Towards Impulse Buying ...supporting
confidence: 93%
“…This means that an individual who has a tendency to buy impulsively will create an impulsive buying behavior in another individual. This study is in accordance with the previous research by Moayery, Narvaiza Cantín, and Gibaja Martíns (2019) where the tendency to buy impulsively is the most influential factor in determining an individual's impulsive buying behavior. Atulkar & Kesari (2018) also revealed that impulse buying tendencies are closely related to consumer impulse buying behavior, where high impulse buying tendencies can make consumers decide to make purchases spontaneously, without any hesitation, and unexpectedly.…”
Section: Influence Of Impulse Buying Tendency Towards Impulse Buying ...supporting
confidence: 93%
“…For example, there was evidence that reduction strategies and interventions could reduce impulse purchases (Dholakia, 2000). The literature on resistance to impulse buying demonstrated that several personality variables could restrain impulse buying, such as self‐control (Efendi et al, 2019; Iyer et al, 2020; Moayery et al, 2019; Sultan et al, 2012), prevention focus (Freitas da Costa et al, 2018), mindfulness (Dhandra, 2020), self‐monitoring (Sharma et al, 2010; Sultan et al, 2012) and dignity (Bandyopadhyay, 2020; Dhandra, 2020). Some of the situation variables that prevented impulse buying had a continuous mitigating impact (Dholakia et al, 2005; Sultan et al, 2012), experiences after impulse purchase (Mittal et al, 2018; Spiteri Cornish, 2020), and crowding in space (Bandyopadhyay, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, conflict monitoring can be deemed as a fundamental cognitive function supporting the process through which control is recruited (Yeung, 2014). In this regard, prior research has shown that self-monitoring is associated with a wide range of behaviors including improved weight management, healthy dietary change (see Spring et al, 2020), and spending behaviors (for a review, see Moayery et al, 2019a). Nevertheless, a person may temporarily fail to experience a self-control conflict (i.e., self-monitoring failure; Hofmann and Kotabe, 2012).…”
Section: Self-monitoring Failuresmentioning
confidence: 99%
“…However, this commentary argues that these methods do not explain how impulses emerge or how researchers can measure them. To address this issue, I encourage researchers to follow a growing body of psychological literature that aims to conceptualize selfcontrol as a psychological process and not as a unitary phenomenon (Hofmann and Kotabe, 2012;Hofmann et al, , 2014Moayery et al, 2019a). More especially, this body of research aims to shed light on the underlying psychological process rather than focusing on the ultimate outcome variable (e.g., food consumption) (Hofmann et al, , 2014.…”
Section: Recommendations For Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation